Predictive index for moderate to severe disability due to migraine - Andrés José Quesada Vázquez; Alexis Álvarez Aliaga; Julio César González Aguilera (Centro Provincial de Información de Ciencias Médicas, 2018)
A cases and control study  was carried out in patients with migraine, diagnosed by means of a cross-sectional study  in Bayamo municipality, Granma province, between January, 2007 to December, 2009, with the objective of creating and validating a predictive index for the risk of developing moderate to severe disability due to migraine. The creation of the index included the selection of risk factors and the calculation of its values.  A quantitative index was obtained which was subdivided in 4 categories of risk, while the validity was satisfactory in all the evaluated aspects. This index demonstrated to have good discriminative capacity (area under the curve ROC 0.937) and it allowed to diagnose correctly 89.74 % of the patients, with sensibility of 86.74 % and specificity of 91.12 %. The Kappa index between observers was 0.950 (p=0.000), the global index was 0.965 (p=0.000) and the coefficient Alpha of Cronbach, 0.627.